Implementation of a Web-Based e-Discipline System at Madrasah Aliyah - Dian Fathur Rohmah; Setya Raharja (AL-ISHLAH: Jurnal Pendidikan, 2024)
Schools play a pivotal role in fostering good character; however, issues concerning student discipline persistently challenge this educational objective. Traditional methods, such as physical logbooks for recording disciplinary infractions, have proven inefficient and ineffective. In response, this study examines a newly implemented web-based application designed to manage and disseminate information regarding disciplinary violations. Employing a descriptive qualitative research methodology, this investigation explores the functionality and impact of the web-based disciplinary system. Preliminary findings indicate that the application utilizes a points-based system to monitor and regulate student behavior, categorizing infractions and accumulating points which may result in sanctions. Additionally, the study highlights efforts by educational institutions to promote rule compliance through comprehensive engagement strategies involving students, parents, and the wider community. These strategies include extensive rule socialization and targeted individual counseling for students demonstrating challenging behaviors. This approach not only streamlines the disciplinary process but also enhances the overall educational environment by reinforcing behavioral standards and accountability.